Where and with whom do you wanna meet?: Session-based collaborative work - Arantes, Flávia Linhalis; Moraes, Claudia Roberta de; Silva, Salomão Henrique Pereira; Fortes, Renata Pontin M.; Pimentel, Maria da Graça C. (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2010)
In this paper we revisit the concept of session applied to collaborative work and define a set of operators to manipulate session information related to workspaces and tools scheduling in collaborative environments. By means of a proof-of-concept implementation which uses web services and context-aware tools, we show an example of how session information provided by the operators can be used to leverage the ubiquitous capabilities of collaborative applications.